2017
DOI: 10.3389/fmicb.2017.02024
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Antibiotic Resistance Genes and Fecal Indicators Varies Intra and Inter-Storm during Combined Sewer Overflows

Abstract: Combined sewer overflows (CSOs) degrade water quality through the release of microbial contaminants in CSO effluent. Improved understanding of the partitioning of microbial contaminants onto settleable particles can provide insight into their fate in end-of-pipe treatment systems or following release during CSO events. Sampling was performed across the hydrograph for three storm events as well as during baseflow and wet weather in three surface waters impacted by CSO. qPCR was performed for select antibiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Viability qPCR methods have been used to target pathogens and fecal indicators with positive correlations observed between vPCR and cultivation methods (Li et al, 2014;Varma et al, 2009). Thus, the utility of this fecal marker gene as an indicator gene for ARGs is not clear, consistent with our previous observations during combined sewer overflows (Eramo et al, 2017a). The BacHum marker was also observed infrequently in the water column downstream from WWTPs.…”
Section: Total and Viable-cell Gene Concentrations In Wwtp Effluent Asupporting
confidence: 61%
“…Viability qPCR methods have been used to target pathogens and fecal indicators with positive correlations observed between vPCR and cultivation methods (Li et al, 2014;Varma et al, 2009). Thus, the utility of this fecal marker gene as an indicator gene for ARGs is not clear, consistent with our previous observations during combined sewer overflows (Eramo et al, 2017a). The BacHum marker was also observed infrequently in the water column downstream from WWTPs.…”
Section: Total and Viable-cell Gene Concentrations In Wwtp Effluent Asupporting
confidence: 61%
“…This suggests that abundance of an ARG at the metagenomic level (total DNA) does not necessary correlate with abundance of the actively transcribed gene (mRNA). The low abundance of transcribed ARGs may also suggest that even though genomic studies have highlighted sewer systems as hotspots of ARGs [ 2 , 4 , 5 , 7 , 9 ], the proliferation of ARGs do not scale linearly with the proliferation of antibiotic-resistant bacteria. Therefore, the use of metagenomic approaches to estimate abundance of antibiotic resistance bacteria in sewer systems will most likely result in overestimation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overflows that mobilize sediment in addition to wastewater would shift the active microbial hazard. Previous end-of-pipe studies of combined sewer overflow (CSO) outfalls demonstrated that attached and suspended microbes can be released at different times during storms [ 9 ]. This same research showed the presence of clinically relevant bacterial classes in CSOs including Clostridia, Bacteroidia, and Epsilonproteobacteria [ 9 ]; however, these data were obtained using DNA-based techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an emerging environmental and human health issue in the world today is the antibiotics resistant bacteria ( Eramo et al, 2017 ; Zhu et al, 2017 ). Infectious bacteria resistant to antibiotics increase the costs of human health and increase the mortality of humans ( Cao et al, 2016 ; Miller et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%